1985
DOI: 10.1038/317355a0
|View full text |Cite
|
Sign up to set email alerts
|

T-cell clones specific for myelin basic protein induce chronic relapsing paralysis and demyelination

Abstract: Experimental allergic encephalomyelitis (EAE) serves as a model for autoimmune diseases mediated by T lymphocytes. Following sensitization to rat, mouse or guinea pig myelin basic protein (MBP) in complete Freund's adjuvant, inbred mouse strains PL/J (H-2u), SJL/J (H-2s) and (PL/J X SJL/J)F1((PLSJ)F1) develop EAE. Whereas sensitization to the N-terminal 37 amino-acid peptide of rat or guinea pig MBP [MBP(1-37)] induces EAE in PL/J mice, immunization to the C-terminal peptide (89-169) leads to EAE in SJL/J mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
244
0
2

Year Published

1989
1989
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 503 publications
(254 citation statements)
references
References 25 publications
8
244
0
2
Order By: Relevance
“…In mice, immunocytochemical studies demonstrated CD4 + T cells in the CNS in relapses of CR-EAE (Traugott et al, 1986;Baker et al, 1990) and radio-labelling has demonstrated passively transferred cells in the nervous system, especially in perivascular cuffs, in CR-EAE in SJL/J mice (Cross et al, 1990). These studies, together with the present study which clearly demonstrates an influx of CD4 + T cells into the CNS in the second episode of CR-EAE, suggest that CD4 + T cells, the effector cells in acute EAE (Pettinelli and McFarlin, 1981;Zamvil et al, 1985), continue to be important in relapses of CR-EAE.…”
Section: Discussionsupporting
confidence: 72%
“…In mice, immunocytochemical studies demonstrated CD4 + T cells in the CNS in relapses of CR-EAE (Traugott et al, 1986;Baker et al, 1990) and radio-labelling has demonstrated passively transferred cells in the nervous system, especially in perivascular cuffs, in CR-EAE in SJL/J mice (Cross et al, 1990). These studies, together with the present study which clearly demonstrates an influx of CD4 + T cells into the CNS in the second episode of CR-EAE, suggest that CD4 + T cells, the effector cells in acute EAE (Pettinelli and McFarlin, 1981;Zamvil et al, 1985), continue to be important in relapses of CR-EAE.…”
Section: Discussionsupporting
confidence: 72%
“…The preferential involvement of the spinal roots with sparing of the peripheral nerves may be due to the reduced blood-nerve barrier in the roots (Olsson, 1968) and the almost 3-fold higher concentration of P 1 in the spinal root than in the peripheral nerve in the rat (Greenfield et al, 1973). In mice, CNS demyelination has been described in EAE passively transferred by MBP-specific lymph node cells, T cell lines and T cell clones (Raine et al, 1984;Zamvil et al, 1985;Tabira and Sakai, 1987) and in EAE passively transferred by proteolipid-protein-specific T cell lines (Satoh et al, 1987). The reported sparing of the PNS in mice with passively transferred MBP-EAE (Raine et al, 1984;Tabira and Sakai, 1987) could be due to interspecies differences in the blood-nerve barrier, Ia antigen expression, or MBP concentration in the spinal roots or to differences in MBP epitopes in intact CNS and PNS myelin in the mouse.…”
Section: Discussionmentioning
confidence: 99%
“…Passive EAE was originally induced by the direct transfer of lymph node cells from animals sensitized to whole spinal cord (Paterson, 1960). More recently, techniques have been described for the in vitro augmentation of donor lymphocyte activity (Panitch and McFarlin, 1977;Richert et al, 1979), and these have ultimately led to the development of MBP-specific T cell lines and clones which are capable of transferring disease in low doses (Ben-Nun et al, 1981;Ben-Nun and Cohen, 1982;Zamvil et al, 1985). EAE, either actively or passively induced, may have an acute or a chronic relapsing course, but each form produces the same neurological signs, namely tail paralysis and limb ataxia, weakness and paralysis.…”
Section: Introductionmentioning
confidence: 99%
“…3, demonstrated that T cell lines could induce EAE (14). Specific T cell clones were then produced that could induce relapses and remissions characteristic of early MS (15). Now inbred animals carrying the T cell receptors for such clones have been genetically engineered, making it possible to take a programmed mouse off the rack, which will get EAE spontaneously (16).…”
mentioning
confidence: 99%